Inheritance of determinate growth habit in fenugreek (Trigonella foenum-graecum L.) - Jhorar, Ram Avtar, B S (Journal of Spices and Aromatic Crops, 2002)
Inheritance of determinate growth habit in fenugreek (Trigonella foenum-graecum L.) was examined in six generations of the reciprocal crosses of HM 350 with NLM and HM 65. All the F1 plants had indeterminate growth habit in both the crosses. In F2, segregation was observed in 3 : 1 ratio for indeterminate and detenninate plant types revealing that determinate habit was under the control of a single recessive gene. The results were further confirmed by observing 1 : 1 ratio in back crosses involving HM 350 as one of the parents.